2021
DOI: 10.3390/mi12111378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microstructure on Micro-Mechanical Properties of Composite Solid Propellant

Abstract: This study was aimed at determining the effect of microstructure on the macro-mechanical behavior of a composite solid propellant. The microstructure model of a composite solid propellant was generated using molecular dynamics algorithm. The correlation of how microstructural mechanical properties and the effect of initial interface defects in propellant act on the macro-mechanics were studied. Results of this study showed that the mechanical properties of propellant rely heavily on its mesoscopic structure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…When the strain to a certain value, the propellant is in the nonlinear region, at which time th stress growth with strain slows down slightly, indicating that the stiffness of th decreases. According to reference [26], microcracks or micropores begin to app the interface in the loading direction, that is, "dewetting" occurs in the nonline It indicates that larger particles are prone to dewetting, and the dewetting site fir in the larger particles and larger particles aggregation area. In the larger partic gation area, the interaction between the particles leads to stress bridging, resu stress concentration phenomenon, leading to more serious dewetting [27].…”
Section: Mechanical Response Analysismentioning
confidence: 99%
“…When the strain to a certain value, the propellant is in the nonlinear region, at which time th stress growth with strain slows down slightly, indicating that the stiffness of th decreases. According to reference [26], microcracks or micropores begin to app the interface in the loading direction, that is, "dewetting" occurs in the nonline It indicates that larger particles are prone to dewetting, and the dewetting site fir in the larger particles and larger particles aggregation area. In the larger partic gation area, the interaction between the particles leads to stress bridging, resu stress concentration phenomenon, leading to more serious dewetting [27].…”
Section: Mechanical Response Analysismentioning
confidence: 99%
“…Belli et al 25 found that in ceramic materials, a high crystal aspect ratio is usually more resistant to fracture than a low crystal aspect ratio, and proposed to improve the mechanical properties of glass‐ceramics by appropriately increasing the crystal aspect ratio. It has been found that the differences in the mechanical properties of materials with similar chemical compositions are mainly due to differences in their microstructure 26–28 . The orientation, distribution, shape, ratio of glassy to crystalline phases and the homogeneity of the distribution determine the bending strength and fracture toughness of glass‐ceramics 29–31 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the differences in the mechanical properties of materials with similar chemical compositions are mainly due to differences in their microstructure. [26][27][28] The orientation, distribution, shape, ratio of glassy to crystalline phases and the homogeneity of the distribution determine the bending strength and fracture toughness of glassceramics. [29][30][31] Feng et al 32 demonstrated that by manipulating the sintering process, in situ crystal formation can cause some grains to grow into elongated grains with a high length-to-diameter ratio, resulting in a microstructure comparable to that of fiber or whisker-reinforced composites.…”
mentioning
confidence: 99%